The interplay between BDNF and PGC-1 alpha in maintaining brain health: role of exercise - Bi, Xuecui; Fang, Jing; Jin, Xin; Thirupathi, Anand (Frontiers in Endocrinology, 2024)
Throughout our evolutionary history, physical activity has played a significant role in shaping our physiology. Advances in exercise science have further reinforced this concept by highlighting how exercise can change gene expression and molecular signaling to achieve various beneficial outcomes. Several studies have shown that exercise can alter neuronal functions to prevent neurodegenerative conditions like Parkinson’s and Alzheimer’s diseases. However, individual genotypes, phenotypes, and varying exercise protocols hinder the prescription of exercise as standard therapy. Moreover, exercise-induced molecular signaling targets can be double-edged swords, making it difficult to use exercise as the primary candidate for beneficial effects. For example, activating PGC-1 alpha and BDNF through exercise could produce several benefits in maintaining brain health, such as plasticity, neuronal survival, memory formation, cognition, and synaptic transmission. However, higher expression of BDNF might play a negative role in bipolar disorder. Therefore, further understanding of a specific mechanistic approach is required. This review focuses on how exercise-induced activation of these molecules could support brain health and discusses the potential underlying mechanisms of the effect of exercise-induced PGC-1 alpha and BDNF on brain health.